57.1k views
5 votes
Find the equation of tangent normal to the curve y=3x-x^3 at points where it cuts the x-axis​

User TheJerm
by
5.0k points

1 Answer

2 votes

Correct Question:-

Find the equations of lines normal to the curve
\rm{y=3x-x^3} at points where it cuts the x axis.


\quad

Solution:-

The given curve,


\longrightarrow\rm{y=3x-x^3}

Differentiating wrt x we get,


\longrightarrow\rm{(dy)/(dx)=3-3x^2}

This term is slope of tangent on the curve at a point (x, y).

Taking reciprocal,


\longrightarrow\rm{(dx)/(dy)=(1)/(3-3x^2)}

and multiplying by -1,


\longrightarrow\rm{-(dx)/(dy)=(1)/(3x^2-3)}

Now this term is slope of normal on the curve at a point (x, y).


\longrightarrow\rm{n(x)=(1)/(3(x^2-1))}


\quad

The points where the curve
\rm{y=3x-x^3} cuts x axis is obtained by equating y = 0.


\longrightarrow\rm{0=y}


\longrightarrow\rm{0=3x-x^3}


\longrightarrow\rm{0=x(3-x^2)}


\longrightarrow\rm{0=x(\sqrt3-x)(\sqrt3+x)}


\Longrightarrow\rm{x\in\left\{-\sqrt3,\ 0,\ \sqrt3\right\}}

So the points where the curve cuts x axis are (-√3, 0), (0, 0) and (√3, 0).


\quad

Consider the point (-√3, 0).

The slope of normal at this point is,


\longrightarrow\rm{n(-\sqrt3)=(1)/(3((-\sqrt3)^2-1))}


\longrightarrow\rm{n(-\sqrt3)=(1)/(6)}

Then equation of normal at this point is,


\longrightarrow\rm{y-0=(1)/(6)(x+\sqrt3)}


\longrightarrow\bf{x-6y+\sqrt3=0}


\quad

Consider the point (0, 0).

The slope of normal at this point is,


\longrightarrow\rm{n(0)=(1)/(3((0)^2-1))}


\longrightarrow\rm{n(0)=-(1)/(3)}

Then equation of normal at this point is,


\longrightarrow\rm{y-0=-(1)/(3)(x-0)}


\longrightarrow\bf{x+3y=0}


\quad

Consider the point (√3, 0).

The slope of normal at this point is,


\longrightarrow\rm{n(\sqrt3)=(1)/(3((\sqrt3)^2-1))}


\longrightarrow\rm{n(\sqrt3)=(1)/(6)}

Then equation of normal at this point is,


\longrightarrow\rm{y-0=(1)/(6)(x-\sqrt3)}


\longrightarrow\bf{x-6y-\sqrt3=0}


\quad

Hence the equations of lines normal to the curve
\rm{y=3x-x^3} at points where it cuts x axis are,


\longrightarrow\left\{\begin{array}{ll}\bf{x-6y-\sqrt3}&\bf{=0}\\\bf{x+3y}&\bf{=0}\\\bf{x-6y+\sqrt3}&\bf{=0}\end{array}\right.

User Brian Noguchi
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.